Efeito da corticoterapia sistêmica crônica no desenvolvimento da periodontite apical em ratos - Nascimento, Isabelly Vidal do (2017)
The apical periodontitis is one of the most prevalent oral diseases in the world. The pathogenesis of the disease is very complex, involving many factors related to the immune response, such as immune cells recruitment, release of inflammatory mediators and the periapical bone resorption. The use of chronic systemic corticosteroids may be directly related to a change in the developmental biology of apical periodontitis, which may influence its prognosis and treatment. Therefore, the objective of this study was to evaluate the inflammatory response and the development of apical periodontitis in rats chronically treated with glucocorticoids. Male Wistar rats (Rattus novergicus) were randomly divided into two groups: a prednisone (5 mg / kg / day) treated group and a control group that was given saline solution for 30 days prior to the induction of apical periodontitis, continuing until euthanasia (0, 7, 14 or 28 days after induction of the lesion). The jaws were submitted to radiographic evaluation (lesion size), and posterior histological (type and intensity of inflammation), histomorphometric (osteoclast counts, polymorphonuclear, mononuclear counts), histochemistry (evaluation of the percentage of collagen fibers) and immunohistochemistry (Interleukin 1β) analyses were performed. All analyzes were performed using GraphPad Prism 5.0® software, at a significance level of 95%. There was a significant increase in apical lesion size at day 14 of prednisone-treated animals (p <0.001). Also on day 14, the prednisone group had an acute inflammatory profile (p= 0.007), significantly different from that presented on the saline group, and the intensity of the inflammatory infiltrate of the prednisone group was higher than that of the saline group (p = 0.007). Polymorphonuclear cells (p = 0.006), osteoclast (p = 0.001) and IL-1β-immunolabelled cells counts (p = 0.044) were higher in animals treated with prednisone on the 14th day. The prednisone group also had a decrease in type I collagen (p=0,040) deposition and an increase in type III collagen (p=0,039) on the 28th day. Therefore, the glucocorticoids may alter the development of experimental apical periodontitis induced in rats, causing an early increase in periapical bone resorption and pulpal necrosis. These drugs may also lead to an exacerbation of the acute inflammatory process, as well as an increase in IL-1β and osteoclast levels, as well as a change in the collagen profile of apical connective tissues.